Robust Virtue Epistemology and the Ontology of Complete Competences - Gómez Alonso, Modesto (Logos. Anales del Seminario de Metafísica, 2021)
In Judgment and Agency, Ernest Sosa argues for a triple-S structure of complete competences that includes, besides the innermost seat competence of the agent, her overall intrinsic condition (shape) and the right situational factors for the manifestation of cognitive success to occur. Complete competences are context-sensitive. The question is raised whether epistemic competences are extrinsic or intrinsic dispositional properties, as well as whether knowledge is the manifestation of powers of the actual world or whether it is a matter of what happens in modally close worlds. An ontological background for the context-sensitivity of epistemic competences that is compatible with their intrinsic character is set in the context of a general account of dispositions. An actualist conception of knowledge is also provided. On this view, the modal force of knowledge, far from being captured by non-localized possibilities, is rooted in the directedness of powers. This article, thus, aims at making explicit the ontological underpinnings of knowledge in a way that it is consistent with Sosa’s fully dispositional virtue epistemology. To this end, the constitution of complete competences is placed in a proper perspective.